Persepsi pesakit terhadap perkhidmatan di jabatan kecemasan Hospital Universiti Sains Malaysia - Rahman, Nor Asikin Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2006)
A cross-sectional study has been done about patient's perception towards service in Emergency Department. There were 83 respondents selected to fulfill the effectiveness of the study. The aim of the study was to identify the factors related contribute in patient perception regarding service in Emergency Department. The study take place in Hospital Universiti Sains Malaysia. The study was to acknowledge the population studied. Based from the study, the highest score among these factors are knowledge followed by accessibility, waiting time and the service in Emergency Department. Patient were satisfied with the effectiveness of the service, flexibility hours of service and the knowledge about the department functioning 24 hours a day.